A case study of exploring the barriers of pro-environmental behaviour. (4th July 2019) - Piispanen, Ville-Veikko; Aromaa, Eeva; Henttonen, Kaisa
The research focuses on the barriers of pro-environmental behaviour in a circular economy. More specifically, the aim is to study how an entrepreneur makes sense of existing barriers when reflecting on the business. Previous studies on environmental awareness and behaviour have focused extensively on the individual and business level, yet barriers resulting from a circular economy have not been studied in small- and medium-sized businesses. In this single case study, the gap is explored by innovating a reflective circular economy diagnostics tool and interviewing one entrepreneur in an energy and resource-intensive industry, which has many established and deep-rooted historical industrial practices. Content analysis and sensemaking practices have been used to analyse the data. The findings show that the barriers are mostly related to economics, and they can be structural, cultural, and contextual. The analysis also shows that pro-environmental concerns do not always lead to pro-environmental behaviour.